Reviewing and renewing the use of beneficial root and soil bacteria for plant growth and sustainability in nutrient-poor, arid soils - Khan, Noor; Humm, Ethan A.; Jayakarunakaran, Akshaya; Hirsch, Ann M. (Frontiers in Plant Science, 2023)
A rapidly increasing human population coupled with climate change and several decades of over-reliance on synthetic fertilizers has led to two pressing global challenges: food insecurity and land degradation. Therefore, it is crucial that practices enabling both soil and plant health as well as sustainability be even more actively pursued. Sustainability and soil fertility encompass practices such as improving plant productivity in poor and arid soils, maintaining soil health, and minimizing harmful impacts on ecosystems brought about by poor soil management, including run-off of agricultural chemicals and other contaminants into waterways. Plant growth promoting bacteria (PGPB) can improve food production in numerous ways: by facilitating resource acquisition of macro- and micronutrients (especially N and P), modulating phytohormone levels, antagonizing pathogenic agents and maintaining soil fertility. The PGPB comprise different functional and taxonomic groups of bacteria belonging to multiple phyla, including Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria, among others. This review summarizes many of the mechanisms and methods these beneficial soil bacteria use to promote plant health and asks whether they can be further developed into effective, potentially commercially available plant stimulants that substantially reduce or replace various harmful practices involved in food production and ecosystem stability. Our goal is to describe the various mechanisms involved in beneficial plant-microbe interactions and how they can help us attain sustainability.